DESAIN DAN PEMBUATAN PERANGKAT PEMBENTUK PENGGANTUNG PAKAIAN BENTUK S BERSUDUT 90o - Syamsul Hadi; Mochamad Muzaki; Purwoko Purwoko; Anggit Murdani; Fica Aida Nadhifatul Aini; Febryan Candra Shakti; M Rio Alfi Sya'bana; Radhi Nurvian Amrullah (P3M Politeknik Negeri Malang, 2025)
The problem lies in the inconsistency of the dimensions of the 90° S-shaped clothes hanger forming device for use in research requiring bending and deflection forces using the Tarno Grocki compression testing machine. This community service project aims to develop a 90° S-shaped clothes hanger forming device whose design can be used in research requiring bending and deflection forces using the Tarno Grocki compression testing machine and cannot be used as a stand-alone device without the aid of a hydraulic jack and frame as a production tool in a home industry. The method applied is modifying the design and device so that it can function using the Tarno Grocki compression testing machine and a stand-alone device with the aid of a hydraulic jack as a production tool in a home industry, including the construction of a support table, a trial run, and the donation to partners or home industries. The results of the community service in modifying the 90o S-Shaped Clothes Hanger Forming Device can be used as a production tool by the household industry, so that there is a synergy between State Polytechnic of Malang and the community in producing clothes hangers for the community's needs more efficiently and can meet the needs of the community in general.